The Ginninderra CH4 and CO2 release experiment: An evaluation of gas detection and quantification techniques. (March 2018) - Feitz, Andrew; Schroder, Ivan; Phillips, Frances; Coates, Trevor; Negandhi, Karita; Day, Stuart; Luhar, Ashok; Bhatia, Sangeeta; Edwards, Grant; Hrabar, Stefan; Hernandez, Emili; Wood, Brett; et al.
Graphical abstract: Highlights: Simultaneous comparison of 8 different atmospheric quantification techniques. Majority of blind estimates within 20% of the actual CH4 release rate. Ensemble approach provides better estimate of rate and uncertainty. Potential to map plumes using a single laser and mobile aerial reflector. Abstract: A methane (CH4 ) and carbon dioxide (CO2 ) release experiment was held from April to June 2015 at the Ginninderra Controlled Release Facility in Canberra, Australia. The experiment provided an opportunity to compare different emission quantification techniques against a simulated CH4 and CO2 point source release, where the actual release rates were unknown to the participants. Eight quantification techniques were assessed: three tracer ratio techniques (two mobile); backwards Lagrangian stochastic modelling; forwards Lagrangian stochastic modelling; Lagrangian stochastic (LS) footprint modelling; atmospheric tomography using point and using integrated line sensors. The majority of CH4 estimates were within 20% of the actual CH4 release rate (5.8 g/min), with the tracer ratio technique providing the closest estimate to both the CH4 and CO2 release rates (100 g/min). Once the release rate was known, the majority of revised estimates were within 10% of the actual release rate. The study illustrates the power of measuring the emission rate using multiple simultaneous methods and obtaining an ensemble median or mean. An ensemble approach to estimating the CH4 emission rate proved successful with the ensemble median estimate within 16% for the actual release rate for the blind release experiment and within 2% once the release rate was known. The release also provided an opportunity to assess the effectiveness of stationary and mobile ground and aerial CH4 detection technologies. Sensor detection limits and sampling rates were found to be significant limitations for CH4 and CO2 detection. A hyperspectral imager's capacity to image the CH4 release from 100 m, and a Boreal CH4 laser sensor's ability to track moving targets suggest the future possibility to map gas plumes using a single laser and mobile aerial reflector.